Teaching and learning English grammar research findings and future directions - Christison, MaryAnn; Christian, Donna; Duff, Patricia 1959-; Spada, Nina Margaret (Global research on teaching and learning English, 2015)
An important contribution to the emerging body of research-based knowledge about English grammar, this volume presents empirical studies along with syntheses and overviews of previous and ongoing work on the teaching and learning of grammar for learners of English as a second/foreign language. It explores a variety of approaches, including form-focused instruction, content and language integration, corpus-based lexicogrammatical approaches, and social perspectives on grammar instruction.